If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 3d + -4 = 0 Reorder the terms: -4 + a + 3d = 0 Solving -4 + a + 3d = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + a + 4 + 3d = 0 + 4 Reorder the terms: -4 + 4 + a + 3d = 0 + 4 Combine like terms: -4 + 4 = 0 0 + a + 3d = 0 + 4 a + 3d = 0 + 4 Combine like terms: 0 + 4 = 4 a + 3d = 4 Add '-3d' to each side of the equation. a + 3d + -3d = 4 + -3d Combine like terms: 3d + -3d = 0 a + 0 = 4 + -3d a = 4 + -3d Simplifying a = 4 + -3d
| 1/-1221*43,090 | | 2*y+7=y+17 | | 10n^2= | | ax-x+6=0 | | -5a+b=13 | | 4x+(x*x)=26 | | 6x-16=10x+6 | | x^2+20=x^2 | | -5x+15=-50 | | 9n-7=5n+39 | | log(x)=-4.5 | | 4/15x6 | | 5x+261=x | | 4/15x4 | | 2z+5.4=-12 | | -10+x=57 | | x=29/4 | | 2(4p-1)=-5(4p+6) | | 44=6c-4 | | X=13x+21 | | 5(X-5)=23 | | x^4-x-15=0 | | -1.5x+6.5=3.5 | | 4y^2-20y+43=0 | | -2.8w=5.964 | | 7(a+3)=87.5 | | Y=7mx+b | | 7(x-6)+14=4(x-4) | | -4.1=3c-8 | | .75t+.25(10-t)=.69(10) | | 4r-8+6-6r=-9 | | -9x+25=-7(x-3) |